1982
DOI: 10.1104/pp.70.3.853
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of O2 Consumption Resistant to Cyanide and Its Development by N-Propyl Gallate and Salicylhydroxamic Acid

Abstract: Kinetics ofinhibition ofcyanide-insensitive 02 uptake by n-propyl gallate (PG) (11) have demonstrated that the cyanide-resistant 02 consumption by ground soybean endosperm which is inhibited by SHAM is attributable to lipoxygenase activity. Hence, the ability of SHAM to uniquely inhibit a single enzyme, i.e. the 'alternative oxidase,' in vivo is questionable.A large number of workers have implied that an alternative oxidase is active in aged white potato tuber slices (7) and in whole tubers that have been t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…2). This result was consistent with previous kinetic studies which indicated that gallate esters and hydroxamates inhibit the alternative pathway in a mutually exclusive fashion (14,25). The similarities of the results obtained when SHAM was used in place of unlabeled butyl gallate in the binding studies (Fig.…”
Section: Resultssupporting
confidence: 82%
“…2). This result was consistent with previous kinetic studies which indicated that gallate esters and hydroxamates inhibit the alternative pathway in a mutually exclusive fashion (14,25). The similarities of the results obtained when SHAM was used in place of unlabeled butyl gallate in the binding studies (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Inhibitor potency is an important parameter for drug development projects. Derivatives of salicylic acid and of gallic acid are well-known AOX inhibitors [48][49][50] , but are only effective against M. perniciosa at millimolar concentrations 5,7 . We have also recently shown that another AOX inhibitor, N-(3-bromophenyl)-3-fluorobenzamide, has a protective effect in plants against WBD at 200 µM even in the absence of a main respiration inhibitor 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Points represent two independent measurements and the continuous lines are the best fit for a 4-parameter sigmoid function. EC50 = 166 µM (GMP), 918 µM (AMP) and ca. 6.5 mM (ADP).…”
mentioning
confidence: 99%
“…Gallate esters have been shown to exhibit antimicrobial activity; in several cases, propyl gallate may serve as an effective alternative to salicylhydroxamic acid, which is a likely developmental toxicant . Salicylhydroxamic acid works by specifically blocking the activity of alternative oxidase (AOX) in pecan scab and in ethylene-treated tubers …”
Section: Introductionmentioning
confidence: 99%
“…49 Salicylhydroxamic acid works by specifically blocking the activity of alternative oxidase (AOX) in pecan scab 50 and in ethylene-treated tubers. 51 We tested all of these compounds for activity against Aspergillus brasiliensis (mold) and Pseudomonas aeruginosa (Gram negative bacteria)representative microorganisms that the health and personal care product industries use for evaluating preservative efficacy 52,53 over a range of alkyl chain lengths to observe variability in antimicrobial activity, as a function of chain length. Of note, A. brasiliensis has recently been found as a causative agent of keratitis, 54 while P. aeruginosa can cause disease in humans, 55 thus emphasizing the importance and relevance of testing these microbes.…”
Section: ■ Introductionmentioning
confidence: 99%